Mechanisms to Establish Judicial Security in Algeria - Chikh, Nassima (Journal of Legal Studies and Researches, 2022)
Judicial security has national and international dimensions that made it an inevitable necessity of the rule of law, and a real means of establishing the principle of legal security and activating it on the ground. In order for the purpose of its implementation to be achieved, a set of factors must be present that contribute to activating the judicial function, and consolidating the principle of judicial security.